The Relationship between Knowledge for Customer and Service Quality on Customer Satisfaction: A Study on UniKL MITEC Student Services - Firdaus Adrutdin, Khairul; Ali, Azlan; Hassan, Sallaudin; Jaafar, Jimisiah; Syafiqah A Rahim, Nur; Imran Qureshi, Muhammad (International Journal of Engineering and Technology, 2018)
Knowledge for customer roles (KC) in student services is essentially very much important since the linkage of knowledge creation, sharing, dissemination and acquisition would be the value created for the customers. One of the important elements of customer knowledge (CK) is knowledge for customer roles (KC) and it reflects on how the process of knowledge transfer and exchange are conducted for the benefits of customer satisfaction (CS). This study aims to discuss on the relationship of knowledge for customer roles (KC) and service quality dimensions (SQ) on customer satisfaction (CS) in student services environment. In depth study on the customer knowledge (CK) dimension will be conducted in order to identify the level of knowledge of customers on student services and how the process of knowledge transfer and exchange are taking place. The study of service quality dimensions (SQ) in the student services is also conducted in order to identify the element of knowledge transfer and exchange that resides in the service quality RATER dimensions and how it relates to the knowledge for customer roles (KC) and customer satisfaction (CS). In conclusion, the construct of knowledge for customer roles (KC) relationship with the service quality dimensions (SQ) and customer satisfaction (CS) is critically assessed and the empirical studies are to be examined so as to assess on the obtained relationships.